Clinicopathological and therapeutic comparisons of esophageal cancer between China and the USA: a multicenter hospital-based study - Juan Zhu; Lingbin Du; Huizhang Li; Xianhui Ran; Hongmei Zeng; Wenqiang Wei (Journal of the National Cancer Center)
Background: Esophageal cancer (EC) remains a global health challenge due to its poor prognosis. China and the United States of America (USA) represent two distinct epicenters of EC burden. Understanding the EC disparities in these two countries is vital for tailoring prevention strategies, optimizing treatment, and enhancing outcomes in both countries. Yet, there lacks a comprehensive comparison of EC characteristics between the two countries. Methods: In this multicenter, retrospective hospital-based study, we enrolled primary EC patients who received their initial treatment at one of 23 hospitals in China during 2016–2017. Using electronic medical records and cancer registration records, information on demographics, lifestyle, and clinicopathological characteristics (including tumor site, pathology, stage, metastases, differentiation, and treatment) were collected. Additionally, we compared these data with the clinicopathological information of invasive EC patients diagnosed in 2016–2017 from the Surveillance, Epidemiology, and End Results (SEER) database in the USA. Results: A total of 6,658 EC patients in China and 8,555 EC patients in the USA were included finally. 85.5% (n = 5,694) of EC were esophageal squamous cell carcinoma (ESCC) in China, while esophageal adenocarcinoma (EAC) was prominent in the USA (58.9%, n = 5,041). Among EC patients with known staging, the proportion of early stage was higher in China compared to the USA (48.3% vs. 30.5%). Among ESCC patients, early-stage cases were higher in China than in the USA (49.8% vs. 31.8%), while among EAC patients, late-stage cases were higher in China than in the USA (77.3% vs. 68.5%) (all P < 0.001). In China, EC mainly occurred in the middle third (60.2%) of the esophagus, whereas in the USA, it was more common in the lower third (59.9%) of the organ. Compared with EC patients with known metastatic status in the USA, China had fewer cases of lymph node metastases (51.4% vs. 57.7%) and distant metastases (7.9% vs. 33.8%). Regarding treatment, China had more surgical therapy (53.7% vs. 22.6%), less radiotherapy (35.6% vs. 53.3%), and less chemotherapy (46.7% vs. 59.7%) compared to the USA. Conclusions: This study reveals notable disparities in EC between China and the USA, encompassing epidemiological, clinicopathological, and treatment dimensions. These findings provide insight for tailored strategies addressing regional variations in clinicopathological and therapeutic characteristics.